Peran Motivasi Kerja dalam Memediasi Pengaruh Kepemimpinan Kepala Sekolah dan Budaya Kerja terhadap Kepuasan Kerja Guru SD Negeri Sekecamatan Banjarmasin Tengah - Ilham Cahyo; Ahmad Suriansyah; Aslamiah Aslamiah (Media Manajemen Pendidikan, 2026)
Teacher job satisfaction is an important factor in improving the quality of education and is influenced by principal leadership, work culture, and work motivation. This study aims to analyze the effect of principal leadership and work culture on teacher job satisfaction, both directly and indirectly through work motivation. This research employed a quantitative approach using path analysis. The population consisted of 401 teachers, with a sample of 200 teachers selected proportionally. Data were collected through questionnaires and analyzed using descriptive analysis and path analysis. The results show that principal leadership has a positive effect on teacher job satisfaction with a path coefficient of 0.305, work culture 0.180, and work motivation 0.536 as the most dominant effect. In addition, principal leadership affects work motivation with a path coefficient of 0.439 and work culture 0.364. There is also an indirect effect of principal leadership on job satisfaction through work motivation of 0.235, and work culture through work motivation of 0.195. Descriptively, all variables are in the high category. And, work motivation acts as a mediating variable that strengthens the influence of principal leadership and work culture on teacher job satisfaction